THE RISK OF VIOLENT BEHAVIOR : A CASE STUDY - Nyi Rd Mega Aroviani; Susanti Niman (Jurnal Sahabat Keperawatan, 2021)
Background: Risk Violent behavior is an individual condition that will endanger oneself, others, family and society. Individuals at risk of violent behavior need psychiatric nursing care to overcome the nursing problems they experience. This study aims to discuss nursing care comprehensively from assessment to evaluation of clients at risk of violent behavior. Case report: The results of the client have a history of traffic accidents and experienced a collision in the head area but at the request of the family, surgery was carried out. After the accident, the family got changes in the client, namely irritability, tantrums, talking and smiling by themselves and seeing things that were not tangible. The implementation of nursing is given to clients in the form of physical exercises: deep breaths and hitting the pillow mattress, assertive exercises and spiritual exercises. The client's family is given nursing education about how to care for the client. The nursing evaluation found that the client was able to do physical exercise and assertive exercise. Families can recognize problems and motivate clients to do the exercises that have been taught by the nurse. Conclusion: The risk of violent behavior is one of the mental nursing problems that can be found in clients with mental disorders with a history of head trauma.